An IoT-based Production Monitoring System for Assembly Line in Manufacture - Mustafha, Muhamad Danial Amzar; M. Thamrin, Norashikin; Che Abdullah, Syahrul Afzal; Mohamad, Zulfakri (International Journal of Integrated Engineering, 2020)
In industry, a contamination in the product requires testing, inspection, diagnosis, repair and then more testing before the plant goes back on the production line. This process can take days and even months, depending on the type and extent of the contamination. Industries also need to ensure that the product can be manufactured in great quantity without any problems. The production time is very important to produce one product to ensure that the target number of products is achieved. The key to overcome this problem is to invent a device that can take care of the time management for this production. Therefore, a monitoring system for a worker in an assembly line is developed to solve this problem by using the IoT system. It adopts Arduino Mega as a microcontroller and IR sensor as a sensory input to detect the parts or products. It is also equipped with Liquid Crystal Display (LCD) to display the timer to guide the worker on the required production working time for one part in the assembly line. Besides that, ESP 8266 is also used to send data to the cloud for data storage and further data analysis. It is found that, with the implementation of this system in an assembly line, the efficiency of the worker is increased approximately around 4.5 percent. Furthermore, with the IoT system, it allows data to be transferred to the smart phone.